(untitled) (American Journal of Islam and Society, 1991)
The Western view of the role of women in Muslim societies presents a strikingly ambivalent attitude. On the one hand, the patrilineal, patriarchal structure of the Muslim family has been so emphasized that it is believed to be at the heart of the assumed subordination of women in Muslim societies (Rassam 1983; Joseph 1985). On the other hand, a matrilineal structure is believed to exist in at least some Muslim societies. Frantz Fanon speaks of how the French colonizers of Algeria developed a policy built on the “discoveries” of the sociologists that a structure of matriarchal essence did indeed exist. These findings enabled the French to define their political doctrine, summed up by Fanon as: “If we want to destroy the structure of Algerian society, its capacity for resistance, we must first of all conquer the women, we must go and find them behind the veil where they hide themselves, and in the houses where the men keep them out of sight” (Fanon 1965, 39). France’s success or failure in adopting this policy, and the repercussions of the adoption of this formula, are beyond the scope of this paper. What is important here is its implication vis–vis the importance of women. Also, it enables us to be cognizant of a structured irony in the politics of studying Muslim women, whether for practical colonial purposes, or for intellectual orientalist aims. In the case of women, for example, French colonialists tried to use them to destroy the structure of Algerian society by attributing to them an almost absolute “significance.” On the other hand, orientalists have used Muslim women also, but with the aim of destroying the image of Islam by rendering them absolutely “insignificant” within the religion. The view of Islam as a purgatory for women underlies most works written on Muslim women. They are commonly depicted as isolated from men, passive actors in the so-called public domain, confined to their kin groups, and so ...